Coronavirus and vulnerable people : addressing the divide in harm and responses and exploring implications for a more peaceful world - Finley, Laura L.; Hall, Pamela D. (Peace education., 2022)
"Drawing from many disciplinary areas, this edited volume explores how the Coronavirus pandemic has disproportionately harmed vulnerable and marginalized people in the U.S.. Chapters address harm to people of color that exacerbated structural racism and harm to low-wage workers that highlighted existing inequalities. In addition, the volume provides strategies that have been successful in mitigating these harms and recommendations for a post-pandemic more peaceful and just future."